Gender at the centre of our research - Bioversity International (2017)
The following factsheet outlines how Bioversity International addresses gender issues in its research projects. First, we carry out ‘gender-responsive research’ by applying a gender lens to other research disciplines, such as climate change or nutrition. Second, we conduct ‘strategic gender research’ as a specialized exploration of gender relations and biodiversity. Third, we strive to make our research ‘gender transformative’ by supporting practices and policies that reshape the dynamics between men and women in ways that have more equitable outcomes. The factsheet provides examples of case studies to illustrate each approach.